Detection of ultrawideband radar signals scattered from complex targets - Immoreev, I.J.; Fedotov, D.V. (Радиофизика и радиоастрономия, 2002)
The questions of detection of radar-tracking signals are discussed, which parameters are unknown. The method for detection of radar signals which parameters are unknown is considered. The method is based on correlation processing of signals received in the adjacent periods of sounding – the interleaved periodic correlation processing (IPCP). Обсуждаются вопросы приема радарных сигналов сопровождения, параметры которых неизвестны. Рассмотрен метод обнаружения радарных сигналов с неизвестными параметрами. Метод основан на корреляционной обработке принятых в смежные периоды зондирования сигналов – межпериодной периодической корреляционной обработке сигналов (IPCP). Обговорено питання приймання радарних сигналів супроводження з невідомими параметрами. Розглянуто метод виявлення радарних сигналів з невідомими параметрами. Метод базується на кореляційній обробці прийнятих сигналів у суміжних періодах зондування – міжперіодна періодична кореляційна обробка сигналів (IPCP).